History and theology in the Gospels: Seventh International East-West Symposium of New Testament Scholars, Moscow, September 26 to October 1, 2016 - Nicklas, Tobias; Niebuhr, Karl-Wilhelm; Seleznëv, Michail; König, Judith; Draughon, Rebecca (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
Cover -- Title -- Introduction -- Table of Contents -- I. Opening Paper and Plenary Discussion -- Metropolitan Hilarion - The "Demythologization" of New Testament Studies (Opening Paper) -- Carl R. Holladay - The Session in Retrospect: Plenary Discussion -- William Loader/Francis Watson/Joel Marcus - Responses -- Metropolitan Hilarion - Counter Response -- II. Main Papers -- Joel Marcus - History and Theology in Matthew -- Vladan Tatalović - The Matthean Passion Narrative in Serbian Interpretation -- Francis Watson - History and Theology in Mark -- Cosmin Pricop - Between Criticism and Patristics: The Transfiguration Story in Mark from an Eastern Point of View -- Carl R. Holladay - The Lukan Travel Narrative: History and Theology in Luke's Gospel -- David P. Moessner - The Problem of the Continuity of Acts with Luke, the Church's Reception of Two Separated Volumes, and the Construction of Luke's 'Theology': Toward a Theology of Jesus the "Christ" of Israel and the "Lord of All" in the Light of the Worldwide Church (ἡ ἐκκλησία) of Luke's 'Gospel Acts' -- Margareta Gruber - "… but he was acting in the temple of his body": Symbolic Performance of Death and Resurrection in the Cleansing of the Temple (John 2:13-23) -- Anatoly A. Alexeev - The Gospel of John: From Christology to Theology -- Armand Puig i Tàrrech - The Figure of Jesus According to the Canonical Gospels -- Stefanos Alexopoulos - The Gospel Narrative in Byzantine Liturgy -- Tobias Nicklas - History and Theology in the Non-Canonical Gospels -- III. Seminar Papers -- Ekaterina Matusova - A New Translation of Ps 78:2 (77:2 LXX) in Matt 13:35 -- Lauri Thurén - The Final Countdown: The Last Judgment in the Light of Narratology and Argumentation Analysis -- Petr Marecek - The Function and Importance of Matthew 28:16-20 in the Gospel of Matthew.